Modalitas Calon Legislatif Perantau Minangkabau pada Pemilu Legislatif Tahun 2019: Modalities of Minangkabau Migrant Legislative Candidates in the 2019 Legislative Election - Novendra Hidayat; Arry Bainus; Caroline Paskarina; Affan Sulaeman (Society, 2022)
This research discusses the modalities in the victory of migrant Minangkabau candidates in the 2019 Legislative Election. Minangkabau is one of the ethnic groups in Indonesia synonymous with a matrilineal kinship system and an institutionalized tradition of migrating. Migrating is a valuable capital utilized by Minangkabau migrant Legislative Candidates to gain support for votes in electoral contests. The research was conducted on two Minangkabau migrant Legislative Candidates who took part in the contestation in the Legislative Elections for the House of Representatives of the Republic of Indonesia. The research method is qualitative with a case study type. Data were collected through interviews with Minangkabau migrant candidates, voting communities, and people involved in winning candidates, such as traditional leaders and the Minangkabau community in the realm and overseas. The results of the research concluded that Fadli Zon (Gerindra Party Legislative Candidate, Electoral District of West Java V) and Jon Erizal (National Mandate Party Legislative Candidate, Electoral District of Riau I) as two of the Minangkabau migrants, the legislative candidates for the House of Representatives of the Republic of Indonesia succeeded in utilizing existing social capital and successfully elected in the 2019 Legislative Election 2019 contestation overseas. Both are considered to have good leadership figures, able to carry out the mandate, and caring, humane, and responsible individuals. Joined in the same social entity, namely the network of Minangkabau migrants who gather through the Minangkabau migrant community, the Minangkabau Family Association. Fadli Zon became General Chairman of the Central Executive Board of the Minangkabau Family Association, and Jon Erizal served as Vice General Chairman of the Riau Minangkabau Family Association. Besides building intensive communication with the community in the election contestation.